Global Factors, Unemployment Adjustment and the Natural Rate - Ron P. Smith; Gylfi Zoega (Economics: The Open-Access, Open-Assessment E-Journal, 2008)
OECD unemployment rates show long swings which dominate shorter business cycle components and these long swings show a range of common patterns. Using a panel of 21 OECD countries 1960-2002, we estimate the common factor that drives unemployment by the first principal component. This factor has a natural interpretation as a measure of global expected returns, which is given added plausibility by the fact that it is almost identical to the common factor driving investment shares. We estimate a model of unemployment adjustment, which allows for the influence both of the global factor and of labour market institutions and we examine whether the global factor can act as a proxy for the natural rate in a Phillips Curve. In 15 out of the 21 countries one cannot reject that the same natural rate, as a function of the global factor, appears in both the unemployment and inflation equations. In explaining both unemployment and inflation, the global factor is highly significant, suggesting that models which ignore the global dimension are likely to be deficient.
Keywords: E2; J1; 330; Unemployment dynamics; labour market institutions investment; principal components; global factors; Arbeitslosigkeit; Konjunktur; Arbeitsmarktflexibilisierung; Natürliche Arbeitslosigkeit; Phillips-Kurve; Faktorenanalyse; Schätzung; OECD-Staaten